Melejitkan Linguistic Intelegence melalui Gemar Membaca - Rahman, Muzdalifah M (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Linguistic Intelligence, a person’s ability and sensitivity to interpret thewording, is able to use words effectively, both orally and in writing. Intelligence of this type are identified by Gardner much involved in reading, writing, speaking,and listening. Reading ability is influenced by several factors, including 1) fluency in reading, 2) the ability to hear, 3) the ability to see, 4) environmental influences, 5) emotional factors, and 6) the child’s intelligence. Some of these factors so as to be an influence in the child’s reading ability, therefore, in this case the reading ability of emotion is always enhanced by a variety of ways, as for how that can be achieved are: 1) read children books from birth, 2) encourage children to talk about what has been heard or read, 3) taking children to the bookstore or library, 4) purchase books that attract children, 5) set aside the money to buy books for children, 6) to set aside money to buy books for children, 7) watch movies as well as buy books according to the film, 8) creates a family library at home, 9) exchange of books belonging to the child by his friend, 10) removes inhibitors such as TV and Playstation, 11) to give the reward to enlarge the spirit of reading child, 12) to make the book as a reward for kids, 13) make reading a daily activity, 14) to dramatize the contents of the book that was read to the child, and 15) make their own books.